The Effect of Hotel Service Satisfaction on Loyalty: The Role of Gender - Adila Sosianika; Lina Setiawati; Nono Wibisono; Lusianus Kusdibyo; Dwi Suhartanto; Agustinus Februadi; Martin Elliott-White (Politeknik Negeri Bandung, 2021)
This study aims to analyze the effects of hotel services satisfaction on three aspects: service product, service delivery, and service environment as well as on the loyalty. There are 210 respondents employed as the sample who visited the hotel in the past month. The analysis technique used is the Structural Equation Model with Partial Least Square. The results showed that all satisfaction variables for hotel services significantly influenced loyalty in both groups of genders. Based on gender difference, it shows that male groups are more interested in service environment satisfaction and service delivery satisfaction towards loyalty, while female groups are more interested in service environment satisfaction and service product satisfaction towards loyalty.